Analysis of dynamic capabilities and company performance antecedent variables in PT PLN (persero) power plant sub-holding - Yusuf, Mujahidin; Atmoko, Andreo Wahyudi (Jurnal Ekonomi, 2024)
This study investigates the variables of resources, knowledge management and learning, alliances, entrepreneurial orientation with dynamic capabilities and performance at the Generation Company PT PLN (Persero). Dynamic capabilities are also examined as mediation variables. The approach uses survey methods and hypotheses tested using PLS-SEM. The analysis results show that showing resources do not affect dynamic capbilities and dynamic capbilities cannot mediate the relationship to company performance. Other variable antecedents, namely knowledge and learning management, strategic alliances, entrepreneurial orientation, and environmental dynamism positively affect dynamic capabilities and dynamic capabilities can mediate relationships with company performance.